Aqueous Gold Overgrowth of Silver Nanoparticles: Merging the Plasmonic Properties of Silver with the Functionality of Gold. Issue 50 (21st November 2017) - Mayer, Martin; Steiner, Anja Maria; Röder, Falk; Formanek, Petr; König, Tobias A. F.; Fery, Andreas
Abstract: To date, it has not been possible to combine the high optical quality of silver particles with the good chemical stability and synthetic convenience in a fully aqueous system, while simultaneously allowing chemical surface functionalization. We present a synthetic pathway for future developments in information, energy and medical technology where strong optical/electronic properties are crucial. Therefore, the advantages inherent to gold are fused with the plasmonic properties of silver in a fully aqueous Au/Ag/Au core–shell shell system. These nanoparticles inherit low dispersity from their masked gold cores, yet simultaneously exhibit the strong plasmonic properties of silver. Protecting the silver surface with a thin gold layer enables oxidant stability and functionality without altering the Ag‐controlled optical properties. This combines both worlds—optical quality and chemical stability—and is not limited to a specific particle shape. Abstract : Optical quality and chemical stability : A general nanoparticle synthesis enables low dispersity and well‐defined shape to be inherited from the masked gold cores, yet simultaneously allows the strong plasmonic properties of silver to be exhibited. Protecting the silver with a thin gold layer enables oxidant stability and surface functionality of this system without altering the silver‐based optical properties.